Reducing Blood Pressure and SRAS Scores in Preoperative CDL Patients Through Alternate Nostril Breathing Exercise (ANBE) - Asni Hasaini; Muhlisoh (Journal of Ners and Midwifery, 2026)
Patients diagnosed with CKD often experience changes in both physiological and psychological responses. Alternate Nostril Breathing Exercise (ANBE) has been reported to influence cardiorespiratory and autonomic functions, as well as to reduce anxiety and stress scores.  The objective of the study was to analyze the effectiveness of ANBE on the stability of physiological and psychological responses in preoperative patients undergoing CDL insertion at Ratu Zalecha Hospital, Martapura. The study employed a quasi-experimental design with a Pretest-Posttest Control Group Design. The total sample size was 30. The instruments used included an observation sheet and the Zung Self-Rating Anxiety Scale questionnaire. The tool required to measure blood pressure is the Omron HEM-7120 digital sphygmomanometer. The data were analyzed univariately with frequency distribution and bivariately with paired t-test and independent t-test. Data were analyzed using univariate and bivariate methods. The result revealed a significant difference in systolic blood pressure between the control group and the intervention group, with a mean ± SD of 179.6±28.45 in the intervention group and 154 ±15.96 in the control group. Similarly, there was a significant difference in diastolic blood pressure between the two groups, with a mean ± SD of 102.47 ± 10.41 in the intervention group and 91.40 ± 7.82 in the control group. In conclusion, ANBE has the potential to serve as a method for managing preoperative stress and physiological responses (such as blood pressure).It is recommended that nurses in inpatient or pre-operative rooms are encouraged to provide brief training and assistance in performing Alternate Nostril Breathing Exercise to pre-operative patients.